Conservative management of placenta percreta. Issue 3 (3rd January 2018) - Matsuzaki, Shinya; Yoshino, Kiyoshi; Endo, Masayuki; Kakigano, Aiko; Takiuchi, Tsuyoshi; Kimura, Tadashi
Abstract: Background: Maternal outcomes after conservative management of placenta percreta are poorly understood. Objective: To assess the success and complication rates of conservative management of placenta percreta. Search strategy: The PubMed, MEDLINE, and Scopus databases were searched for English‐language articles published between January 1990 and December 2016, using combinations of search terms related to conservative management of placenta percreta. Selection criteria: Only studies describing conservative treatment for placenta percreta (without placental removal) were included in the systematic review. Data collection and analysis: There were 44 studies included and maternal outcomes were reviewed and categorized among 72 patients. Main results: The uterus was preserved among 42 (58%) patients and severe complications developed among 40 (56%). Prophylactic uterine artery embolization (UAE) did not improve success rates ( P =0.807); however, the mean time for complete placental resorption was lower in the UAE group than in the non‐UAE group (22.4 weeks vs 35.3 weeks; P =0.014). Hysterectomy was performed at a mean of 44.6 days after cesarean delivery. Among the 23 patients with hysterectomy‐related complications, 18 (78%) experienced bladder injury, intraoperative bleeding (>2000 mL), or both. The use of chemotherapy did not improve success rates ( P =0.064). Conclusions: The present systematic review revealed high maternal morbidity during conservative management of placenta percreta. Abstract : The present systematic review reveals high maternal morbidity during conservative management of placenta percreta.